2019
DOI: 10.1080/17461391.2019.1646811
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intermittent running on biomarkers of bone turnover

Abstract: Intermittent exercise might be an efficient means of exercise for improving bone strength and quality. The aim of our study was to examine the effect of intermittent running on bone turnover markers using altered exercise-to-rest intervals. Twelve males completed one control (no exercise), and three, 45-minute intermittent protocols (5 s, 20 s, and 80 s intervals) matched for distance and speed. Fasted venous blood samples were collected at baseline, 1 h, 2 h and 24 h post-exercise. Carboxyterminal crosslinked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Thus, we will reference research done outside of the menstrual cycle realm to compare our results to in the context of post-exercise β-CTXΙ response. Previous studies have shown conflicting results when measuring β-CTXΙ concentrations from pre-to postexercise 108,109,106,113,156,147,124 , with many showing significant increases and some showing decreases or no change. An increase or decrease in β-CTXΙ could both be osteogenic, with increases representing an upregulation of bone remodelling and reductions indicating a decrease in osteoclastic activity and reduced bone loss, with more potential for bone formation.…”
Section: Pth At Rest and In Response To Exercisementioning
confidence: 97%
See 2 more Smart Citations
“…Thus, we will reference research done outside of the menstrual cycle realm to compare our results to in the context of post-exercise β-CTXΙ response. Previous studies have shown conflicting results when measuring β-CTXΙ concentrations from pre-to postexercise 108,109,106,113,156,147,124 , with many showing significant increases and some showing decreases or no change. An increase or decrease in β-CTXΙ could both be osteogenic, with increases representing an upregulation of bone remodelling and reductions indicating a decrease in osteoclastic activity and reduced bone loss, with more potential for bone formation.…”
Section: Pth At Rest and In Response To Exercisementioning
confidence: 97%
“…Several studies unrelated to the menstrual cycle have shown contradicting results in regard to β-CTXΙ levels to intermittent exercise or prolonged endurance exercise, paired with minimal response of bone formation marker P1NP. This makes it difficult to assess what the long term net effects of these results may be 113,124,108,125,126,127 .…”
Section: Ctx Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results from the few studies that have included a running intervention and a control group are inconsistent. Two studies reported no significant differences in bone formation marker P1NP levels 1-24 h hours after an intermittent [ 15 ] or a continuous [ 16 ] bout of running compared to a non-exercise control condition, but Alkahtani et al [ 17 ] reported increases in P1NP immediately and 24 h after intermittent running. In terms of bone resorption, increases in β-CTX-1 have been shown 1 h, but not 24 h, after intermittent running [ 15 ] and 24-96 h after continuous running [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported no significant differences in bone formation marker P1NP levels 1-24 h hours after an intermittent [ 15 ] or a continuous [ 16 ] bout of running compared to a non-exercise control condition, but Alkahtani et al [ 17 ] reported increases in P1NP immediately and 24 h after intermittent running. In terms of bone resorption, increases in β-CTX-1 have been shown 1 h, but not 24 h, after intermittent running [ 15 ] and 24-96 h after continuous running [ 16 ]. Potential explanations for these discrepant results include differences in exercise regimen (i.e., duration, intensity, intermittent/continuous) and measurement error (i.e., instrumentation and biological noise), and lack of standardisation of factors such as sleep, diet, physical activity prior to and following the running bout.…”
Section: Introductionmentioning
confidence: 99%